The value of repeated CT in monitoring the disease progression in moderate COVID-19 pneumonia: A single-center, retrospective study. Issue 10 (12th March 2021) - Gao, Yang; Hu, Yuxiong; Zhu, Junteng; Liu, Huan; Qiu, Rongxian; Lin, Qunying; He, Xiongzhi; Lin, Hai-Bin; Cheng, Shiming; Li, Guangxi
Abstract : Abstract: The role of thoracic CT (computerized tomography) in monitoring disease course of COVID-19 is controversial. The purpose of this study is to investigate the risk factors and predictive value of deterioration on repeatedly performed CT scan during hospitalization. All COVID-19 patients treated in our isolation ward, from January 22, 2020 to February 7, 2020, were reviewed. Patients included were categorized into RD (Radiological Deterioration) group or NRD (No Radiological Deterioration) group according to the manifestation on the CT routinely performed during the hospitalization. All clinical data and CT images were analyzed. Forty three patients were included in our study. All are moderate cases with at least 4 CT scans each. Eighteen (42.9%) patients had radiological deteriorations which were all identified in CT2 (the first CT after admission). Patients in RD group had lower leukocyte count ( P  = .003), lymphocyte count ( P  = .030), and higher prevalence ( P  = .012) of elevated C-reactive protein (CRP) at admission. NRD patients had a lower prevalence of reticulations ( P  = .034) on baseline CT (CT1, performed within 2 days before admission) and a longer duration between symptom onset and the time of CT2 ( P  < .01). There was no significant difference in hospital stay or fibrotic change on CT4 (follow-up CT scan performed 4 weeks after discharge) between 2 groups. Shorter duration between symptom onset and CT2 time (odds ratio [OR], 0.436; 95% confidence interval: 0.233–0.816; P  < .01) and lower leukocyte count in baseline evaluation (OR, 0.316; 95% CI: 0.116–0.859; P  < .05) were associated with increased odds of radiological deterioration on CT image during hospitalization. For moderate COVID-19 patients, the value of routinely performed CT during the treatment is limited. We recommend avoiding using CT as a routine monitor in moderate COVID-19 patients.